THE LINKAGE BETWEEN AGEING, MIGRATION AND RESILIENCE: RESILIENCE AMONG YOUNG-OLD TURKISH AND MOROCCAN IMMIGRANTS. (11th November 2018) - Klokgieters, S S; van Tilburg, T G; Deeg, D J H; Huisman, M
Abstract: The structure of immigrants' life is considered discontinuous with less predictable key biographical events. Labour immigrants in Western Europe are affected by adversities from migration affecting their wellbeing. Based on 23 life story interviews with Turkish and Moroccan immigrants living in the Netherlands aged 60 and older, resilience is investigated. Resilience is the process by which individuals cope effectively with adversity using resources. The study illustrates a link between ageing conditions, migration and resilience. Circumstances in which individuals foster resilience collide with four live stages: settling in the host society, negotiating their stay, third age, and fourth age. When investments in resources made in one stage, more resources are transferred into the next stage. Resources include having had an education in the country of origin, early investment in language skills, having two incomes, acceptance through meaning of migration and religion, strong family networks, and ability to sustain a circular lifestyle.